2011
DOI: 10.1177/147323001103900620
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketamine with Remifentanil for Improving the Quality of Anaesthesia and Recovery in Paediatric Patients Undergoing Middle-Ear Ventilation Tube Insertion

Abstract: Intraoperative patient movement scores were significantly lower, and surgeon satisfaction scores were significantly higher, in the KR group than in the K group. Time to recovery was significantly shorter in the KR group than in the K group. In conclusion, remifentanil was a good adjuvant to ketamine, improving the quality of anaesthesia and postoperative recovery in children undergoing MEVTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…14 , 15 Lee et al evaluated the effects of ketamine with remifentanil to improve the quality of anesthesia and postoperative recovery, following brief procedures in pediatric patients undergoing middle-ear ventilation tube insertion. 6 They reported a lower patient movement scores, higher surgeon satisfaction scores, and shorter time to recovery in ketamine-remifentanil group compared with only ketamine group.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…14 , 15 Lee et al evaluated the effects of ketamine with remifentanil to improve the quality of anesthesia and postoperative recovery, following brief procedures in pediatric patients undergoing middle-ear ventilation tube insertion. 6 They reported a lower patient movement scores, higher surgeon satisfaction scores, and shorter time to recovery in ketamine-remifentanil group compared with only ketamine group.…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies, ketamine combined with either propofol or remifentanil has been used safely in children. 4 , 6 However, when ketamine is used in combination with propofol or remifentanil, children may still become in pain or discomfort, disoriented, and movement during the procedure. 4 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that local anesthesia can be successfully used for TTI in older children, particularly those aged 5 years and older, while face-mask inhalation or intravenous anesthesia was more commonly used in preschool-aged children. In clinical practice, however, it is currently standard to perform TTI under intravenous anesthesia using ketamine, facemask inhalation anesthesia, or both [ 4 ], despite potentially dangerous side effects. For example, children requiring TTI often have an upper respiratory tract infection, which increases the risk of laryngospasm with inhalational anesthesia [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%